Use of Moisturizers and Lubricants for Vulvovaginal Atrophy - Sarmento, Ayane Cristine Alves; Kamilos, Márcia Farina; Costa, Ana Paula Ferreira; Vieira-Baptista, Pedro; Eleutério, José; Gonçalves, Ana Katherine (Frontiers in Reproductive Health, 2021)
The estrogen decrease in postmenopausal women results in functional and anatomical changes in the genitourinary tract. The most prevalent and bothersome symptoms are vaginal dryness, dyspareunia, and reduced lubrication, which can significantly affect the quality of life of these women, principally those who are sexually active. Hormonal therapy with local estrogens is generally considered the “gold standard.” However, there are cases in which there are clinical concerns about its use or women opt for non-hormonal options. Thus, safe and effective non-hormonal options are needed to improve symptoms in these women. Moisturizers and lubricants are first-line therapy for breast cancer survivors.